2024
DOI: 10.1039/d4fo00381k
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of insect protein sources on intestinal health and disease: insights from human ex vivo and rat in vivo models

Helena Segú,
Florijan Jalševac,
Marta Sierra-Cruz
et al.

Abstract: The exploration of edible insects, specifically Alphitobius diaperinus and Tenebrio molitor, as sustainable sources of protein for human consumption is an emerging field. However, research into their effects on intestinal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Dietary glutamate and aspartate are metabolized during intestinal transport to various products, including urea metabolites. 74 , 75 In this regard, previous findings from our group showed that insect supplementation in rats ameliorates LPS-altered urea levels in plasma, 37 reinforcing the link between L-amino acid levels reaching the jejunum and plasma urea levels. Thus, the correlations observed in our study raise the possibility that the activation of umami intestinal taste receptors could play a role in the regulation of nitrogen metabolism.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Dietary glutamate and aspartate are metabolized during intestinal transport to various products, including urea metabolites. 74 , 75 In this regard, previous findings from our group showed that insect supplementation in rats ameliorates LPS-altered urea levels in plasma, 37 reinforcing the link between L-amino acid levels reaching the jejunum and plasma urea levels. Thus, the correlations observed in our study raise the possibility that the activation of umami intestinal taste receptors could play a role in the regulation of nitrogen metabolism.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously shown that LPS-intestinal-induced inflammatory stimulus caused an inflammatory profile at intestinal and peripheral levels that is in some respects ameliorated by insect consumption. 37 In this paper, we have investigated the impact of LPS on intestinal taste receptors and explored the effects of insect consumption in this inflammatory scenario. Our results revealed that the injection of LPS had minimal impact on the assessed intestinal taste receptors, with minor significant changes observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations